Forgery Attack to an Asymptotically Optimal Traitor Tracing Scheme - WU, Yongdong (Institutional Knowledge at Singapore Management University, 2007)
In this paper, we present a forgery attack to a black-box traitor tracing scheme [2] called as CPP scheme. CPP scheme has efficient transmission rate and allows the tracer to identify a traitor with just one invalid ciphertext. Since the original CPP scheme is vulnerable to the multi-key attack, we improved CPP to thwart the attack. However, CPP is vulnerable to a fatal forgery attack. In the forgery attack, two traitors can collude to forge all valid decryption keys. The forged keys appear as perfect genuine keys, can decrypt all protected content, but are untraceable by the tracer. Fortunately, we can patch this weakness with increasing the decoder storage.